EVALUASI DALAM PEMBELAJARAN BAHASA ARAB - Ubaid Ridho (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2018)
This article explains the importance of evaluation as one of the learning components, particularly in Arabic teaching and learning. In the learning process there are two main activities, namely learning done by the students and teaching done by the teacher, the two activities are to achieve the objectives set out in the lesson plan. In this article, readers are invited by the author to discuss various matters related to the evaluation of Arabic learning, such as the objectives and principles of evaluation, the variety of evaluation, and the signs in the preparation of test equipment, whether test or non test techniques. Artikel ini menjelaskan tentang pentingnya evaluasi sebagai salah satu komponen pembelajaran, utamanya dalam kegiatan belajar mengajar bahasa Arab. Dalam proses pembelajaran ada dua kegiatan utama, yaitu belajar yang dilakukan oleh peserta didik dan mengajar yang dilakukan oleh guru, dua kegiatan tersebut adalah untuk mencapai tujuan yang telah ditetapkan dalam rencana pembelajaran. Dalam artikel ini, pembaca diajak penulis untuk berdiskusi tentang berbagai hal terkait evaluasi pembelajaran bahasa Arab, diantaranya adalah tujuan dan prinsip evaluasi, ragam evaluasi, dan rambu-rambu dalam penyusunan alat tes, baik teknik tes atau non tes.